Subject/ive bodies: the resistance poetics of Chrystos and Mahadai Das. (11th June 2021) - MacDonald, Geoffrey
Abstract : Recent criticism has considered how literary texts harness historical and ideological forces in the representation of the body. However, much of that scholarship focuses on hegemonic structures such as Western medicine, post-human technologies or colonial race theories. This article looks at how two poets from the Americas – Indigenous North American Chrystos (Menominee) and Mahadai Das from Guyana – express representations of the body from a position of marginalisation to emphasise the connections between individual subjectivity and social transformation. I discuss the body as theme for producing a resistance poetry that directly connects desire, disaffection, sexuality and mourning to decolonisation. I perform close readings that emphasise the linkages between intimate relations and social movements. Chrystos and Das speak to a constitutive divide in post-colonial studies between the personal and political in what is called resistance literature. By centring deeply personal perspectives on decolonial struggle within a figurative context that encourages contemplation and complexity, these poets contribute to a diversification of resistance theory that addresses gender, anti-racist, sexual diversity and other movements of the last few decades.